STRUCTURAL ANALYSIS OF WASTE SEPARATION MACHINE FRAME USING FEA METHOD - Fathur Rohman; Dani Mardiyana; Fabrobi Ridha; Satish Kumar Damodar (Nusa Putra University, 2023)
Waste has become a significant problem that requires significant management. Automatic waste separator machine technology has been developed by many countries to help with waste management efficiency. The working principle of the automatic waste separator is to separate the types of organic and non-organic waste. In making the machine frame, this must be taken into account carefully. Here the Autodesk Inventor 2021 application is used to analyze the strength of the frame of an automatic garbage separator. In the frame strength analysis simulation, the type of material used is ASTM A36 Steel with a U-shaped iron plate profile with a thickness of 6 mm. The total load on the frame is 284.5 kg. The static simulation results show that the maximum von misses stress is 138.285 MPa with a maximum displacement of 16.28 mm. while the value of safety factor is 1.4 ul. Based on the results of the simulation analysis, the value of the safety factor is included in the value range (1.25 -2.0) and the value of von misses â‰¤ 200 MPa (Modulus of elasticity) for ASTM A36 material, which means that the frame design for the waste separator machine meets good safety standards.